Evaluation of probability distribution models for stutter ratios in the typing system of GlobalFiler and 3500xL Genetic Analyzer. (September 2021) - Manabe, Sho; Fujii, Koji; Fukagawa, Takashi; Mizuno, Natsuko; Sekiguchi, Kazumasa; Inoue, Kana; Hashiyada, Masaki; Akane, Atsushi; Tamaki, Keiji
Highlights: Stutter ratios should be considered in DNA evidence interpretation. Detectable stutters are back, forward, double-back, and minus 2-nt stutters. We experimentally reevaluated probability distribution models for stutter ratios. We proposed the weighted average of longest uninterrupted stretch (LUS) values. The models can be used in software programs for DNA evidence interpretation. Abstract: As DNA typing systems have become increasingly sensitive in recent years, probability distribution models for back, forward, double-back, and minus 2-nt stutter ratios have been desired to be considered in DNA evidence interpretation using specific software programs. However, experimental investigations have been insufficient, especially for forward, double-back, and minus 2-nt stutters. In this study, we experimentally reevaluated the probability distribution models for each stutter ratio in the typing systems of GlobalFiler™ PCR Amplification Kit and 3500xL Genetic Analyzer from Thermo Fisher Scientific. In addition, to enhance the reliability of longest uninterrupted stretch (LUS) values and corrected allele numbers used in previously developed models for stutter ratios using sequence information (i.e., LUS model and multi-seq model ), we propose the weighted average of LUS values and corrected allele numbers based on the number of observations in sequence-based population data. Back stutter ratios demonstrated a positive correlation with allele numbers ( allele model ) in eight loci, LUS values ( LUS model ) in eight loci, and corrected allele numbers ( multi-seq model ) in five loci. The forward stutter ratios (FSRs) of D22S1045 followed the LUS model . FSRs other than D22S1045 and double-back stutter ratios followed the LUS model by considering multiple loci together. Minus 2-nt stutter ratios observed in SE33 and D1S1656 did not increase with the increase in the allele numbers. The adopted models for each stutter ratio can be implemented in software programs for DNA evidence interpretation and enable a reliable interpretation of crime stain profiles in forensic caseworks.